TERAPI OKSIGEN TERHADAP PERUBAHAN SATURASI OKSIGEN MELALUI PEMERIKSAAN OKSIMETRI PADA PASIEN INFARK MIOKARD AKUT (IMA) - Budi Widiyanto; L. S. Yamin - (Universitas Muhammadiyah Semarang, 2014)
Background: Acute myocardial infarction is the death of heart muscle cells due to prolonged ischemia due to coronary artery occlusion in. One of the measures for the prevention of myocardial infarction is oxygen therapy. Oxygen therapy aims to maintain adequate tissue oxygenation fixed and can reduce myocardial work due to lack of oxygen supply. Thisstudy was conducted to determine the effect of oxygen therapy on the value of oxygen saturation through oximetri examination in patients of acute myocardial infarction (AMI) in the emergency room in Dr. Moewardi hospital Surakarta. Method: This study used quantitative research using pre-experimental design with one group pre test-post test design. Samples involved in this study amounted to 38 respondents using Quota Sampling.Result: The results showed that prior to oxygen therapy oxygen saturation values obtained all the respondents were 38 (100%) experienced mild hypoxia, and after being given oxygen therapy obtained a total of 32 (84.2%) of respondents who experienced an increase in oxygen saturation of mild hypoxia and as many as 6 (15.8%) respondents remained inmild hypoxia. Results of statistical tests using the Wilcoxon test significance value p = 0.000 (p = <0,05). Making the hypothesis Ho is rejected which means no effect of oxygen therapy to changes in oxygen saturation values through oximetri examination in patients acute myocardial infarction (AMI).Suggest: Given the importance of oxygen therapy in patients with acute myocardial infarction, it is expected that the role of nurses to monitor all the time and consider providing oxygen therapy to a higher concentration of eg nonrebreathing mask with a mask (NR) to improve the process of ventilation with FiO2 higher.